Urgensi Ijtihad Ekonomi Pada Era Globalisasi - Amir Mu'allim; M. Roem Syibly (Unisia, 2011)
Globalization has changed the fabric of human life and lead to accelerated economic development islam as a religion rahmatan ill alamin is required to always be ready to provide solutions to various issues, because not every economic problem in the modern era has been arranged in al-Quran and al-Hadith, then opened the door of ijtihad. Method of economic ijtihad has very important position, because products of globalization are very fast and diverse. The classical scholars have provided a good example of how diligence in the economic field that should be followed by the scientists of this modern era. In the current era, the most appropriate economic ijtihad is the collective ijtihad as has been done by the DSN-MUI, Bahsul Masail NU, and Majelis Tarjih Muhammadiyah. However, should also noted how economic ijtihad products that now exist can be mutually reinforcing and contribute to the repertoire of minimal economic sciences of Islam, not the other way would lead to disunity.Keywords: Economic Ijtihad, Islamic economics, globalization, maslahah.